2002
DOI: 10.1034/j.1399-5448.2002.30107.x
|View full text |Cite
|
Sign up to set email alerts
|

Urinary excretion of n-acetyl-β-d -glucosaminidase and retinol binding protein as alternative indicators of nephropathy in patients with type 1 diabetes mellitus

Abstract: Diabetic nephropathy (DN) is usually characterized by glomerular dysfunction, with microalbuminuria as an early indicator. Urinary excretion of smaller molecular weight proteins such as n-acetyl-beta-glucosaminidase (beta-NAG) and retinol binding protein (RBP) indicate proximal tubular dysfunction, and may identify diabetic patients at risk of developing diabetic nephropathy. In a trial to assess renal tubular function, urinary excretion of beta-NAG (by colorimetric assay) and RBP (by ELISA) were determined in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 16 publications
3
55
0
2
Order By: Relevance
“…[30] Increased urinary NAG excretion is one of the most sensitive markers of renal disease and suggests that the cell injury is in the renal proximal tubules. [30][31][32] This was also supported by renal histological changes in LPS-treated animals.…”
Section: Discussionmentioning
confidence: 66%
“…[30] Increased urinary NAG excretion is one of the most sensitive markers of renal disease and suggests that the cell injury is in the renal proximal tubules. [30][31][32] This was also supported by renal histological changes in LPS-treated animals.…”
Section: Discussionmentioning
confidence: 66%
“…43,44 Increased urinary levels of retinol-binding protein have been found in a pediatric population of type 1 DM patients with and without microalbuminuria, signifying that this marker may be used to detect early tubular damage. 45 In a recent prospective study that followed type 2 DM patients for an average of 30 months, urinary retinol-binding protein appeared to be an independent predictor of disease progression (risk of dialysis, doubling of serum creatinine or death) after adjusting for confounding factors such as creatinine clearance, proteinuria, and blood pressure. 12 Monocyte chemoattractant protein-1 is a secreted chemokine that is thought to play an important role in the pathogenesis of tubulointerstitial disease by activating macrophage recruitment in diabetic nephropathy.…”
Section: Markers Of Tubulointerstitial Damagementioning
confidence: 98%
“…Urinary excretion of smaller molecular weight proteins such as N-acetyl-E-D-glucosaminidase (NAG) and retinol binding protein (RBP) indicate proximal tubular dysfunction, and may identify diabetic patients at risk of developing diabetic nephropathy (29). In a trial to assess renal tubular function, Salema et al (29) found that diabetic patients with microalbuminuria had concomitant renal tubular disorder indicated by high urinary NAG and RBP.…”
Section: Significance Of Lysosomal Enzymuria As a Marker Of The Preclmentioning
confidence: 99%
“…In a trial to assess renal tubular function, Salema et al (29) found that diabetic patients with microalbuminuria had concomitant renal tubular disorder indicated by high urinary NAG and RBP. Meanwhile, patients without microalbuminuria had both tubular markers excreted in urine in significantly higher amounts than controls.…”
Section: Significance Of Lysosomal Enzymuria As a Marker Of The Preclmentioning
confidence: 99%